2016
DOI: 10.1111/cch.12318
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver perceptions of childhood weight: demographic moderators and correlates

Abstract: Background To examine whether ethnicity moderates the association between caregiver characteristics and perceptions of childhood weight and whether these perceptions are associated with their child’s obesity. Methods Caregivers recruited from pediatricians’ offices (N=453) completed a survey about childhood health; nurses weighed and measured the children. Caregivers reported their own weight and height, demographic information about their family, and made ratings of healthy weight for children in general an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…These factors have previously been found to impact parents' perceptions of their child's weight status 5,19,37,42,43 and were not measured in this study.…”
Section: Limitations and Strengthsmentioning
confidence: 80%
“…These factors have previously been found to impact parents' perceptions of their child's weight status 5,19,37,42,43 and were not measured in this study.…”
Section: Limitations and Strengthsmentioning
confidence: 80%
“…Noteworthy, two studies reported fair agreement between parent perception of their child weight status and the actual weight status (kappa statistics = 0.214, 0.28 respectively) 6,36 . Another study reported a significant association between parents' misperception and obesity status of their children (OR =1.76, 95% CI= 1.32-2.34 P<0.05) 22 . Furthermore, a couple of studies reported a significant relationship between accurate parental perceptions of their child's weight status and the child's actual weight status (p <.001) 47…”
Section: Parents' Perception Of Their Child's Weight Statusmentioning
confidence: 96%
“…A normal weight percentile is between 5 and 85, while less than five is underweight, overweight is between 85 and 95, and obese is greater than or equal to 95. For analysis of the visual perception of child size, an artist rendering depicting weight as used [29].…”
Section: Research Questions and Statistical Analysis For Eachmentioning
confidence: 99%